2007
DOI: 10.1093/jn/137.4.910
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin and Isorhamnetin Prevent Endothelial Dysfunction, Superoxide Production, and Overexpression of p47phox Induced by Angiotensin II in Rat Aorta

Abstract: The dietary flavonoid quercetin reduces blood pressure and improves endothelial function in several rat models of hypertension. We analyzed the effects of quercetin and its methylated metabolite isorhamnetin on the aortic endothelial dysfunction induced by incubation with angiotensin II (AngII) in vitro for 6 h. AngII diminished the relaxant responses to acetylcholine in phenylephrine-contracted aorta. Coincubation with quercetin or isorhamnetin, or addition of superoxide (O(2)(-)) dismutase or apocynin to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 27 publications
4
71
0
Order By: Relevance
“…Finally, we studied the effects of DiOHF on the expression of NADPH oxidase subunits because some recent studies have reported that flavonoids may modulate NADPH oxidase expression both in vitro and in vivo (Al-Awwadi et al, 2005;Sanchez et al, 2006Sanchez et al, , 2007. Interestingly, we found that DiOHF concentration dependently reduced the protein level of p47phox in differentiated HL-60 cells.…”
Section: Discussionmentioning
confidence: 82%
“…Finally, we studied the effects of DiOHF on the expression of NADPH oxidase subunits because some recent studies have reported that flavonoids may modulate NADPH oxidase expression both in vitro and in vivo (Al-Awwadi et al, 2005;Sanchez et al, 2006Sanchez et al, , 2007. Interestingly, we found that DiOHF concentration dependently reduced the protein level of p47phox in differentiated HL-60 cells.…”
Section: Discussionmentioning
confidence: 82%
“…Further, treatment of phenylephrine-contracted aortic rings with Ang II resulted in decreased relaxation in response to ACh and increased O 2 Ϫ by dihydroethidium (DHE) staining. Treatment of these aortic rings with quercetin/isorhamnitin or SOD/apocynin decreased p47 phox expression and endothelial dysfunction (282).…”
Section: Nistala Et Al 2062mentioning
confidence: 90%
“…The translocation of cytosolic p47 phox to the membrane is essential in the assembly process of this complex and plays a major role in NADPH oxidase activity in VSMCs (Touyz et al, 2003). The previous study has reported that quercetin prevent AngII-induced endothelial dysfunction by inhibiting the overexpression of p47 phox and the subsequent increased O 2˙− production in the medial layer of the vessel (Sanchez et al, 2007). Quercetin that is the main component of TFE, about 45%, as a member of the flavonoid family is widely discussed as an antioxidant.…”
Section: Discussionmentioning
confidence: 98%